Towards mid-infrared fibre lasers: rare earth ion doped chalcogenide glasses and fibres - Sakr, Hesham (2016)
This Project is aimed at developing rare earth ion doped chalcogenide glasses targeting mid-infrared (MIR) fibre lasers, emitting in the wavelength region 4 – 5 μm. The work reported in this thesis has two objectives: (i) a study of the Ge-As-In-Se glass system when doped with a single species of rare earth (RE) ions, i.e. praseodymium (Pr3+) or cerium (Ce3+), or when co-doped with two rare earth ion species: Pr3+ and Ce3+, and (ii) a study of the effect of replacing a gallium (Ga) additive with an indium (In) additive on the physical and optical properties of the undoped and Pr3+ doped Ge-As-(Ga/In)-Se glasses and fibres.